Sequential Hydrogen Tunneling in o‐Tolylmethylene. Issue 71 (12th September 2021) - Lohmiller, Thomas; Sarkar, Sujan K.; Tatchen, Jörg; Henkel, Stefan; Schleif, Tim; Savitsky, Anton; Sanchez‐Garcia, Elsa; Sander, Wolfram
Abstract: o ‐Tolylmethylene 1 is a metastable triplet carbene that rearranges to o ‐xylylene 2 even at temperatures as low as 2.7 K via [1, 4] H atom tunneling. Electron paramagnetic resonance (EPR) and electron nuclear double resonance (ENDOR) spectroscopical techniques were used to identify two conformers of 1 ( anti and syn ) in noble gas matrices and in frozen organic solutions. Conformer‐specific kinetic measurements revealed that the rate constants for the rearrangements of the anti and syn conformers of 1 are very similar. However, the orbital alignment in the syn conformer is less favorable for the hydrogen transfer reaction than the orbital configuration in the anti conformer. Our spectroscopic and quantum chemical investigations indicate that anti 1 and syn 1 rapidly interconvert via efficient quantum tunneling forming a rotational pre‐equilibrium. The subsequent second tunneling reaction, the [1, 4] H migration from anti 1 to 2, is rate‐limiting for the formation of 2 . We here present an efficient strategy for the study of such tunneling equilibria. Abstract : Who is first ? Conformer specificity, although rarely evidenced, is expected to play a crucial role in tunneling reactions. [1, 4] hydrogen transfer in o ‐tolylmethylene is a puzzling example in this respect, as the apparent rate constants do not differ for the two conformers. Our structural, kinetic, and energetic analyses demonstrate that conformer specificity is disguised by a rotational tunneling pre‐equilibrium.